Precipitated Silica from Pumice and Carnondioxide Gas (Co2) in Bubble Column Reactor - Retno Dewati; Suprihatin; Ketut Sumada; Sri Muljani; Meutia Familya; Silviana Ariana (Future Science)
Precipitated silica is a silica product, containing silica, a white powder, a large enough porous and nano particle sized. The precipitated silica products are needed to support the operation of various types of industries such as automotive tire industry, rubber industry, cosmetics industry, electronics industry, agriculture and others. This precipitate silica can be produced by a chemical reaction process between the sodium silicate solution and various types of acids such as hydrochloric, sulfuric, acetate and other acids. In this study, the source of silica was obtained from a pumice while precipitation formation was carried out with the use of carbon dioxide gas (CO2). The sodium silicate solution was obtained by extracting the silica contained in a pumice with sodium hydroxide (NaOH) solution and heated to 100C for 1 hours. The carbon dioxide gas is injected into the aqueous solution of sodium silicate in a bubble column reactor and there is a reaction to form a precipitated silica. Based on research results found that the quality of precipitated silica has a quality: white colors, 85-90% silica content, 12-20% aluminum oxide content and surface area 108-227 m2/g. The